1967
DOI: 10.1084/jem.125.6.1001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the Inhibition of Chemotaxis by Phosphonate Esters

Abstract: Studies in the time course of the response of rabbit polymorphonuclear leukocytes (PMN's) to the complement-associated chemotactic factor have revealed that the response is virtually complete by 60 min with less than 15% additionally responding cells thereafter. Phosphonate esters with a well defined capacity to inhibit serine esterases have been used to study the cell-associated enzymes of the rabbit PMN required for the chemotactic response. Two types of inhibition of the cell response to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
66
0

Year Published

1968
1968
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 9 publications
1
66
0
Order By: Relevance
“…Ward and Becker [29] have recently shown that two cell-bound serine esterases are required for cellular chemotaxis (leukotaxis). One of these esterases exists in, or on, the leukocyte in an activated state.…”
Section: Discussionmentioning
confidence: 99%
“…Ward and Becker [29] have recently shown that two cell-bound serine esterases are required for cellular chemotaxis (leukotaxis). One of these esterases exists in, or on, the leukocyte in an activated state.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological mechanisms controlling neutrophil chemotaxis are unclear, although Ward and Becker (7) suggested that this process may be under the control of a surface serine proteinase. They showed that the inhibition of this enzyme by organophosphorus compounds reduced neutrophil chemotaxis (8,9) but were unsure as to the identity of the natural substrate or inhibitor (10).…”
mentioning
confidence: 99%
“…These findings suggest that the serine proteases involved in the O2 production by human PMN and monocytes are similar to chymotrypsin rather than trypsin, and are possibly located at the cell surface Received for publication 20 April 1979 and in revised form 31 July 1979. 74 cluding chemotaxis, phagocytosis, degranulation, and superoxide (O°) production (1)(2)(3)(4)(5)(6)(7)(8)(9). The available evidence suggests that active and stimulus-activated esterases are required for chemotaxis and phagocytosis (1)(2)(3)(4)(5).…”
mentioning
confidence: 99%
“…The available evidence suggests that active and stimulus-activated esterases are required for chemotaxis and phagocytosis (1)(2)(3)(4)(5). The inhibition profiles of chemotaxis of rabbit polymorphonuclear leukocytes (PMN)l given by the several phosphonate esters indicate that the esterases are similar to chymotrypsin rather than trypsin, although not completely similar to chymotrypsin (1). The chymotrypsin type proteases are also required for the phagocytosis of antigen-antibody complexes by guinea pig peritoneal macrophages (6).…”
mentioning
confidence: 99%